Dal segno al suono. Indagine sulla lettura musicale allo strumento - Odone, Alberto (Milano University Press, 2022)
"From sign to sound" is a research project aimed to investigate some peculiar features of the musical reading with reference to instrumental performance. Its purpose is to extend the present knowledge about cognitive, musical, and pedagogical aspects of the subject, pointing out problematic issues and solutions significant for the young musicians' music performance education. The main study profile, which differentiates it from very few existing international studies on the subject, arises from the particular situation of the Latin countries (to which some other Latin American countries must be added) that adopted, starting from XIX century, the syllabic designation of notes, abandoning the alphabetic one. The aim of the research was to clarify a) the extent to which the outlined situation is widespread in Italian and European instrumental teaching, b) what are the prevailing opinions about it, and c) whether different perspectives can be found based on instrumental families or educational schools.